2001
DOI: 10.1161/01.hyp.38.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Mediates Some of the Renal Actions of Acutely Administered Angiotensin II

Abstract: Abstract-Recent studies suggest that endogenous endothelin mediates much of the vasoconstrictor activity and vascular fibrotic damage caused by chronic administration of angiotensin II. The present study uses the mixed endothelin-A and endothelin-B receptor antagonist bosentan and the endothelin-A-selective blocker BQ-123 to study the contribution of endogenous endothelin to the pressor and renal action of acutely administered angiotensin II in conscious, chronically catheterized rats. Exposure to angiotensin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 34 publications
(37 reference statements)
3
24
1
Order By: Relevance
“…It is evident therefore that adrenomedullin is released from endothelial cells in response to two potent vasoconstrictors, angiotensin-II and endothelin-1. In that some actions of angiotensin-II are via stimulation of endothelin-1 (Riggleman et al 2001, Pollock 2005, it is possible that the adrenomedullin response to angiotensin-II observed in the present study resulted from augmented endothelin-1 production in endothelial cells.…”
Section: Discussionmentioning
confidence: 73%
“…It is evident therefore that adrenomedullin is released from endothelial cells in response to two potent vasoconstrictors, angiotensin-II and endothelin-1. In that some actions of angiotensin-II are via stimulation of endothelin-1 (Riggleman et al 2001, Pollock 2005, it is possible that the adrenomedullin response to angiotensin-II observed in the present study resulted from augmented endothelin-1 production in endothelial cells.…”
Section: Discussionmentioning
confidence: 73%
“…Although Ang II stimulates ET-1 synthesis in endothelial cells, several hours are required for this effect, 3 whereas ET A blockade blunts very rapidly the systemic or renal actions of Ang II in our healthy humans as well as in rats. [12][13][14][15][16] However, release of ET-1 takes place within minutes from in vitro vessels 3,17 or human vascular cultured cells exposed to Ang II, 33 implying that preformed ET-1 is stored in cells and that its release may be Ang II-dependent. 15 Such a mechanism cannot, therefore, be excluded in our human model despite no change in plasma ET-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] However, release of ET-1 takes place within minutes from in vitro vessels 3,17 or human vascular cultured cells exposed to Ang II, 33 implying that preformed ET-1 is stored in cells and that its release may be Ang II-dependent. 15 Such a mechanism cannot, therefore, be excluded in our human model despite no change in plasma ET-1 levels. In fact, plasma ET-1 may not reflect an increase in its tissue concentration due to the preferential release of peptide on basolateral side of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Whereas these studies suggest a relation between Ang II and ET in the long-term regulation of arterial pressure, Riggleman et al have also shown that ET A receptor blockade prevents the renal vasoconstrictor actions of low doses of acutely administered Ang II and the natriuretic and diuretic actions of higher doses of Ang II in the rat. 10 More recently, Montanari et al had reported that an ET A selective antagonist inhibits the acute renal hemodynamic response to Ang II in humans. 11 This same group also provided evidence for ET A -dependent increases in renal vascular resistance in human subjects during AT 1 receptor blockade.…”
Section: Et-1 In Ang II Hypertensionmentioning
confidence: 99%